Initial Assessment on Air Quality from Vehicles Crossing Toll Gate in Highway (Case: Kota Baru Toll Gate, South Lampung) - Sari, Novi Kartika; Ramadani, Fadhil; Prasetio, Bambang; Alifa, Nabila Putri Yandri (Brawijaya University, 2025)
ABSTRACT The Trans-Sumatera Toll Road promotes regional connectivity and economic development, but vehicle activity at toll gates may impact air quality due to emissions and congestion. This study investigates the effect of traffic on air quality at the Kota Baru toll gate, South Lampung. Nitrogen dioxide (NO₂) and carbon monoxide (CO) were measured over four days during the rainy season, following SNI 19-7119.9:2005. NO₂ was analyzed using the Griess-Saltzman method, while CO was detected with a calibrated portable instrument. Meteorological data (wind speed/direction, temperature, humidity) and vehicle volume were also collected to assess their influence on pollutant dispersion. Statistical analyses, including Pearson correlation and Multiple Linear Regression (MLR), were conducted using RStudio. The average NO₂ and CO concentrations were 81.3 ± 26.6 µg/Nm³ and 89.8 ± 30.1 µg/Nm³, respectively. Light-duty vehicles made up 86.5% of total traffic and showed a strong positive correlation with both pollutants (r > 0.6). Winds from the southwest and south (0–3.8 m/s) may carry pollutants northward. Temperature and wind speed were negatively correlated with pollution, while humidity showed a positive correlation (r > 0.5; p < 0.05). Short-term traffic control and long-term air quality monitoring are recommended to support emission reduction and public health. Keywords: air quality assessment, meteorological factors, toll gate, South Lampung